Análisis del índice de morosidad del grupo 8042 de Yanbal Ecuador S.A, periodo enero a julio 2017. - Condoy Proa, Karina Rosario (2017)
The following research work aligned to the regulations of the titling guide of the Technical University of Machala emphasizes the analysis of the delinquency rate of the sales group 8042 that is dedicated to recruiting women to work under the direct selling multilevel modality The commercial company Yanbal Ecuador SA, which has long maintained a high percentage and this is a problem for management. The objective of this paper is to determine the factors that influence the current delinquency rate, which leads to a low level of productivity, and thus to increase revenues. The mechanism used by the company to assist the work of the independent directors Is the Yanbal score, this is a score indicating the probability of payment of an independent consultant, the granting of credit so that the new distributor can start their business has increased sales considerably in recent years, however this tool irresponsibly handled Or unprofessional math can become a drawback when it comes to measuring results. Through the application of the interview we could note that the reasons why this index is because of the lack of timely payment of the consultants and this is because There is no effective collection process for their customers, in addition to not having a productive sale does not obtain Nen income that compensates in work done and this is due to the lack of knowledge of the activity that is done as product advice, demonstration and more. To achieve productive business and the loyalty of the entrepreneur so that she receives an economic incentive that compensates her work by means of professional use of the working tools with which we count is the proposed action plan after having carried out this analysis, for this it must have In mind that permanent training and should be present within the work schedule of the independent director. Since the delinquency ratio is the result of the sum of past due debts of the last 13 divided campaigns for the sum of the net sale of the last 13 campaigns a way to decrease this percentage without doubt increasing the sale. Through bibliographic research in scientific journals and based on the consultation of other monographic works related to our research, the respective basic concepts and support guide were obtained. The multilevel direct selling business is one of the biggest trades in the world market today and our country is no exception, having to take advantage of this apogee is essential to learn the good management of the portfolio. This being the first investigation conducted with this sales group regarding the portfolio report, this will be useful for future investigations of this type to take corrective measures. This work will serve as a guide for all entrepreneurial women who are part of this company and for those who decide to take the opportunity to grow by having their own business and continue to change lives.